Histochemical study of the connective tissue of the dental pulp - Zerlotti, E. (Elsevier, 1964)
This study was concerned with the reactivity and organization of the connective tissue of the dental pulp and with the changes of the tissue colloids during ageing. Newer methods of preparation of the specimens and certain specific histochemical procedures were used. The results indicate that the extracellular matrix of the connective tissue of the dental pulp contains glycoproteins, sialic acid, acid mucopolysaccharides and proteins bearing reactive ε{lunate}-amino groups of lysine-hydroxylysine. The fibres and the ground substance are considered to interact forming coacervates. The extracellular matrix is organized as a heterogeneous colloid containing soluble and insoluble fractions. In young pulps the soluble fraction is large and the tissues are markedly affected by buffer solutions or enzymes. In ageing there is a decrease of the soluble fraction and a change in the aggregation of the tissue colloids. These changes are signalled by the high resistance to buffer solutions and proteolytic enzymes and by the changes in staining of the tissues. The alteration in the internal organization of the proteins probably induces a redistribution of ions and is related to pulp stone formation. © 1964.